Gender Differences in Step and Stride Length among Physiotherapy Students at Holy Family Hospital, Rawalpindi - Hussain, Syed Ali; Afzal, Rabia; Batool, Samina; Khan, Nouman; Khan, Esha; Salman, Amer Dawood (International Health Review, 2025)
Notable gender dimorphism in anatomy shows effects that extend beyond morphology to functional dynamics. Gait, as a major locomotor activity, can demonstrate these differences, especially in such parameters as step length and stride length. To determine whether perceived differences are statistically significant, the current study aims to quantitatively investigate and compare these gait parameters in both male and female participants in order to determine their mutual variability. A group of 50 healthy undergraduate students (13 males and 37 females) was selected based on a pre-determined inclusion criteria. This study was conducted in the Physiotherapy Department of the Holy Family Hospital, Rawalpindi, Pakistan. A small setup was created within the department. The complete procedure and one familiarity trial were performed before the actual data collection. All the participants were told to walk a 10-meter marked distance at a self-paced, comfortable walk. The total number of steps taken from the start to the end point of the 10-meter track were carefully noted down, enabling the computation of the mean step length and stride length. The data was analysed with the help of IBM SPSS (version 17.0). The analysis showed a significant difference between the two groups. The mean step length taken by men was 27.39 ± 1.74 inches, which is larger as compared to the mean step length of women, that is, 25.80 ± 2.31 inches. Stride length also varied, with the mean length for men being 54.79 ± 3.49, as compared to women with the mean length of 51.61 ± 4.62. Further, independent samples t-test established statistically significant differences in both step and stride length (p > 0.05). These findings empirically support the notion that gender is an important predictor of gait dynamics. The male subjects were found to have a longer step and stride length when walking, as compared to their female counterparts, in this cohort. The results underline the need to include biological differences, causing gender differences in ergonomics, rehabilitation, and sports science.